The social impact of the stigma attached to Sars-CoV-2 - Talarico Marçal Galvão, Mariana; Dellalibera-Joviliano, Renata (Seven Editora, 2023)
In the last 2 years, the world has started to live as a hostage to the COVID-19 disease caused by the new Coronavirus (SARS-Cov-2), which has flu-like symptoms. However, the surprise is that the real impacts of the COVID-19 Pandemic go beyond millions of deaths around the world. Thus, the objective of this study was to assess the social impact of the COVID-19 pandemic. DOI: https://doi.org/10.56238/tfisdwv1-009